Прогнозування інноваційного розвитку підприємств олійно-жирової промисловості - Кузьмінська, Наталія Леонідівна (My University, 2014)
Дисертаційну роботу присвячено питанням активізації інноваційного розвитку підприємств олійно-жирової промисловості. З цією метою у роботі приділено увагу трактуванню змісту понять інновація, інноваційний процес, інноваційний розвиток. Досліджено теоретичні аспекти прогнозування інноваційного розвитку. Узагальнено класифікацію методів прогнозування. Проведено аналіз інноваційної діяльності підприємств харчової промисловості України загалом і олійно-жирової зокрема, із застосуванням запропонованих методичних підходів. The thesis is devoted to the oilseed industry enterprise’s innovative development intensification. For this aim, attention is focused on interpretation of the innovation, innovation process and innovation development meanings contents. The theoretical aspects of forecasting innovation development were studied. Classification of forecasting methods was generalized. The analysis of the innovation activity of food industry enterprises in Ukraine generally and oilseed enterprises in particular were made using methodological approaches. The analysis was based on the rating assessment of innovation activities performance indicators and methods of correlation-regression analysis. Main factors which restrain innovation were emphasized. Defining the role of the informational component in the enterprise’s innovative elements development system became the basis for creating organizational and methodological process of the oilseed industry knowledge base formation. Methodological approaches to forecasting trends of oilseed industry and it’s enterprises development, based on sampling factors of innovative development, including the eventual influence, so unlike to existing methods, based on cognitive modeling and semi structured unstable systems intelligent management technology were improved.
Keywords: інновації (олійно-жирова промисловість); innovations (oil and fat industry); інноваційний розвиток підприємства; когнітивне моделювання; олійно-жирова галузь; innovation development; cognitive modeling; oilseed industry; кафедра вищої математики імені проф. Можара В. І.